Correlates of multiple paternity in the Aquatic Warbler (Acrocephalus paludicola) - Dyrcz, Andrzej; Wink, Michael (Journal für Ornithologie, 2002)
SummaryAquatic Warblers show a promiscuous mating system and males do not help the female to incubate eggs or feed nestlings. Paternity was determined in 64 broods in the Biebrza basin (NE Poland) studied in 1993, 1994 and 1997 by microsatellite PCR analysis. A total of 14 broods had been sired by a single male and 50 by two and more males (multiple paternity 78.1%); a maximum of 5 fathers was detected in 4 broods (7.8 % of broods), which indicated that almost every young in these broods had been sired by a different father. Few significant performance differences could be found between broods sired by a single male and ones having several fathers. Broods with single paternity were begun significantly earlier than multipaternal broods. The frequency of multiple paternity varied between years, i. e. 54.5 % in 1993, 87.5 % in 1994 and 92.3 % in 1997. Females with long wings or short bills had broods sired by a larger number of males.
Gesehen am 05.10.2017